1991
DOI: 10.2165/00003088-199120020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Posture and Sleep on the Pharmacokinetics of Paracetamol (Acetaminophen) and Its Metabolites

Abstract: The effects of posture and sleep on the pharmacokinetics of paracetamol (acetaminophen) 500 mg and its metabolites were studied in 8 healthy men. The mean residence times for paracetamol or its metabolites were significantly altered by change in posture or by sleep, whereas other pharmacokinetic parameters were unchanged. The change in mean residence time is consistent with a faster absorption of paracetamol during ambulation. The present data suggest that the proposed posture-related changes in volume of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…The results of Rumble et al on paracetamol suggest that previously reported changes in the volume of distribution do not exist [32]. As a general rule, because distribution is mainly determined by the physico-chemical properties of the administered drug, significant changes due to posture seem unlikely.…”
Section: Effects Of Posture On the Absorption Of Orally Administered mentioning
confidence: 88%
“…The results of Rumble et al on paracetamol suggest that previously reported changes in the volume of distribution do not exist [32]. As a general rule, because distribution is mainly determined by the physico-chemical properties of the administered drug, significant changes due to posture seem unlikely.…”
Section: Effects Of Posture On the Absorption Of Orally Administered mentioning
confidence: 88%
“…The effects on the pharmacokinetics and bioavailability of acetaminophen of such factors as the age [1,2] and sex [1,3] of patients, the excess of body mass [3], the condition of gastro-intestinal tract peristalsis, simultaneous administration with various foods [4,5], and type of motor activity (including prolonged anti-orthostatic hypokinesia) and sleep [6,7] are currently widely studied.…”
mentioning
confidence: 99%
“…Thus, studies of the effect of motor activity on acetaminophen pharmacokinetics [5] found that the pharmacokinetic parameters of the drug changed insignificantly during sleep and bed rest with the execption of MRT, which decreased. Apparently these effects are due to not only a limitation on motor activity but also changes of hemodynamics under ANOH conditions and the neutralizing effect of acetaminophen on glomerular filtration under ANOH conditions.…”
Section: Resultsmentioning
confidence: 99%